PENGARUH REKOMENDASI ANALIS, ORDER IMBALANCE, TRADING VOLUME ACTIVITY, DAN MOMENTUM TERHADAP RETURN SAHAM PADA PERUSAHAAN YANG TERDAFTAR DALAM INDEKS LQ45 PERIODE 2020-2021 - Sigit Setyo Wicaksono; Erman Denny Arfinto; Nana Varian Januardi (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT Stocks present a promising investment opportunity, however, they also come with high risks due to their sensitivity to changes. As the number of stock investors in Indonesia increases, more and more securities analysts are providing recommendations on purchasing shares through various media. This research aims to explore the impact of Analyst Recommendations, Order Imbalance, Trading Volume Activity, and Momentum on Stock Returns for companies listed on the LQ45 Index during the period of 2020-2021. To carry out this study, secondary data was obtained from the Bloomberg Terminal and www.idx.co.id. The researchers utilized purposive sampling, which resulted in a sample of 35 companies that remained listed on the LQ45 Index during the period of 2020- 2021, producing a total of 521 data points. The data were analyzed using multiple linear regression and IBM SPSS Statistics 25 software, which passed all classic assumption tests. The findings suggest that Analyst Recommendations, Order Imbalance, and Trading Volume Activity have a significant positive effect on stock returns. On the other hand, Momentum has a significant negative impact on stock returns. These results highlight the importance of considering these factors when making investment decisions, especially for companies listed on the LQ45 Index.